A global review of consumer behavior towards e-waste and implications for the circular economy - Islam, M.T.; Huda, N.; Baumber, A.; Shumon, R.; Zaman, Atiq; Ali, F.; Hossain, R.; Sahajwalla, V. (ELSEVIER SCI LTD, 2021)
To tackle the alarming increase in e-waste or end-of-life (EoL) electronic products, consumer behavior towards the end of their useful life needs to be thoroughly studied. End users or consumers are the starting point where e-waste starts its journey into several paths within the circular economy (CE), such as repair, reuse, remanufacturing, and recycling. E-waste often ends up in landfill due to improper disposal of e-waste with household waste by consumers. Studying consumer behavior allows for the identification of appropriate approaches to achieve CE. Numerous academic journal papers have been published concerning consumers' e-waste-related knowledge and awareness, and behavior on consumption, disposal, storage, recycling, and repair. Substantial knowledge gap exists around how understandings of consumer behavior around e-waste may be integrated into the CE model. This article aims to reduce this gap by reviewing 109 research papers published in international peer-reviewed journals identified in the Web of Science (WoS) core collection database, using content analysis methodology to analyze and review the articles. The study aims to provide invaluable input for developing a more consumer-centric CE framework for both policymakers and researchers seeking to advance knowledge and implementation strategies around e-waste. This is one of the earliest systematic reviews of studies on consumer behavior around e-waste. The study results show that consumers' disposal and recycling behaviors are the two main areas of research interest in the studies reviewed. In contrast, reuse and repair behavior were investigated to a lesser extent. In this study, several research gaps and areas for future research are identified, along with suggestions for a CE framework focusing on the e-waste sector that, encompasses policy initiatives and business model innovations. The identified studies presented here offer a valuable starting point for researchers who are starting to work on consumer behavior-related e-waste research.